New records of amblyomma multipunctum and amblyomma naponense from ecuador, with description of a. multipunctum nymph - Labruna, Marcelo B.; Martins, Thiago F.; Nunes, Pablo H. [UNESP]; Costa, Francisco B.; Portero, Francisco; Venzal, Jose M. (American Society of Parasitologists, 2013)
We provide new data for the ticks Amblyomma multipunctum and Amblyomma naponense from Ecuador. In addition, we describe the nymph of A. multipunctum for the first time. During December 2012, ticks were collected by dragging in forest trails of 1 locality at Puyo, Pastaza Province (elevation 979 m), and another locality at Papallacta, Napo Province (3,474 m). A total of 10 adults of A. naponense were collected at Puyo, whereas 27 adults and 3 nymphs of A. multipunctum were collected at Papallacta. Compared to sequences of a fragment of the mitochondrial 16S rDNA gene of adult and nymphal ticks, the sequence of an Amblyomma nymph was identical to the sequences generated from the A. multipunctum adults. The 3 collected nymphs (including the 1 used for molecular analysis) had the same morphotype, and were used for the first morphological description of the nymphal stage of A. multipunctum. Sequences generated from the A. naponense specimens were closest (97% identity by BLAST) to a corresponding sequence of A. naponense from Brazil, whereas the A. multipunctum sequences were closer to (90-91% identity) several Neotropical Amblyomma species. Herein, we provide just the second record of A. naponense in Ecuador, more than 100 yr after this tick was reported in this country. Adults and nymphs of A. multipunctum were found in highland, humid montane forest areas, in agreement with the only 2 previous reports of A. multipunctum in Ecuador and Colombia. No genetic differences were found among A. multipunctum ticks that presented significant morphological differences, suggesting intraspecific polymorphism in the adult stages of this species. © 2013 American Society of Parasitologists.